New use for spent coffee ground as an adsorbent for tetracycline removal in water. (January 2019) - Dai, Yingjie; Zhang, Kexin; Meng, Xianbing; Li, Jingjing; Guan, Xueting; Sun, Qiya; Sun, Yue; Wang, Wensi; Lin, Mu; Liu, Mei; Yang, Shengshu; Chen, Yanjun; et al.
Abstract: Spent coffee grounds (SCG-1 and SCG-2) were used to study the adsorption of tetracycline (TC) antibiotics and the effects of adsorption time, initial pH, amount of adsorbent and ionic strength were detected. The TC adsorption isotherm on SCG-1 was compared with SCG-2. The results showed that the removal efficiencies of TC (50 mg/L) of SCG-1 and SCG-2 were 83.1% and 97.2%, respectively, shake for 2 h. The probability of adsorption is high and balances in about 20 min. The estimate of parameters got for TC from the Langmuir isotherm saturated adsorption quantity and adsorption balance constant were 64.89 mg/g, 0.0557 L/mg, respectively for SCG-1 and 123.46 mg/g, 0.4735 L/mg, respectively for SCG-2. The adsorption mechanism might be a π–π interaction that occurs in the interface by hydrogen bonding and the between the TC molecular and the SCGs. At last, we found that SCG has a high adsorption size for TC. Highlights: The adsorptive ability of tetracycline on spent coffee grounds (SCG-1 and SCG-2) was investigated. The adsorption isotherms of tetracycline on SCG-1 and SCG-2 were carried out. The adsorption rate was very quick with the equilibrium of adsorption within about 20 min. This SCG-1 and SCG-2 has high adsorption ability for tetracycline.